2022
DOI: 10.1155/2022/7602992
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Difference of Six Active Constituents of Huangqi Liuyi Decoction between Control and Diabetic Nephropathy Mouse Models

Abstract: Huangqi Liuyi decoction is a famous traditional Chinese medicine (TCM) that has been widely used in China for the management of diabetes since the Song Dynasty. Today, it is commonly used for treating diabetic nephropathy (DN). Our previous experimental studies have suggested that the mixture HQD, containing astragalus saponin, astragalus flavone, astragalus polysaccharide, and glycyrrhetinic acid, could be used for the treatment of DN and to improve renal function. The objective of this study was to develop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Moreover, HQD induced the activity of CYP2E1 in the DN mouse and inhibited the activity of CYP2E1 in the control mouse. The activity of each CYP450 enzyme was consistent with changes in expression (Wang et al, 2022d). However, the specificity of individual CYP enzymes allows for only specific substrates to be metabolized by the enzyme.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, HQD induced the activity of CYP2E1 in the DN mouse and inhibited the activity of CYP2E1 in the control mouse. The activity of each CYP450 enzyme was consistent with changes in expression (Wang et al, 2022d). However, the specificity of individual CYP enzymes allows for only specific substrates to be metabolized by the enzyme.…”
Section: Introductionmentioning
confidence: 62%
“…A previous study by our group found that blood glucose, triglycerides, cholesterol, blood creatinine, urea nitrogen, and 24-h urinary protein were significantly higher in 12-week-old db/db mice compared to control (p < 0.05). Simultaneously, our previous study found that many collagen fibers (blue) were visible in the glomerular basement membrane and tubular interstitium of 12week-old db/db mice, and significantly more than that of the control, with obvious collagen fiber deposition and obvious glomerular and tubular lesions (Wang et al, 2022d). Therefore, 12-week-old db/db mice were used as the mouse model of diabetic nephropathy and db/m mice of the same age were used as the control.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be mentioned that the T max , t 1/2 and MRT of CG, ononin and formononetin in beagle dog plasma were lower than those in rat plasma, while those of astragaloside IV and astragaloside II in beagle dog were a little higher than those in rats (Liu et al, 2014; Zeng et al, 2018). Furthermore, compared with mice, the T max and t 1/2 of CG, ononin and formononetin were a bit faster and shorter in beagle dog (Wang et al, 2022). The results show that the absorption and elimination of CG, ononin and formononetin were slightly faster in beagle dogs than in rats and mice, but those of astragaloside IV and astragaloside II were slower.…”
Section: Resultsmentioning
confidence: 99%
“…Zeng et al developed a UPLC-MS/MS method for formononetin, CG, ononin and astragaloside IV to the pharmacokinetic study of multiple components in rat plasma after intragastric administration of Huangqi decoction (Zeng et al, 2018). Recently, Q. Wang et al established a 12 min HPLC-MS/MS method for the simultaneous quantitation of astragaloside IV, CG, ononin and formononetin to compare the pharmacokinetics of these active constituents in control and diabetic nephropathy mice orally treated with Huangqi Liuyi decoction (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Huangqi Liuyi decoction significantly inhibited glucose reabsorption in renal tubular epithelial cells, decreasing the fasting blood glucose and limiting renal fibrosis in DN rats [ 11 , 12 ]. In pilot studies [ 13 ], we found that several ingredients found in the Huangqi Liuyi decoction, namely, astragalus saponin, astragalus flavone, astragalus polysaccharide, and glycyrrhizic acid (AKA HQD), delayed the development of DN in db/db mice when combined. HQD could significantly decrease the fasting blood glucose (FBG), 24 h urinary protein (24 h U-Alb), urea nitrogen (BUN) serum creatinine (Scr), and triglyceride (TG) in DN mice ( P < 0.05).…”
Section: Introductionmentioning
confidence: 99%